Investing in Leadership Development: the UK Experience - Middlehurst, Robin (International Higher Education, 2012)
This article highlights aspects of the UK's experience of leadership development in higher education over three decades as the sector has sought to respond to growing pressures and significant change. More recently, a Leadership Foundation has been established to support senior leaders and managers and this has further stimulated developmental provision at institutional, national and international levels.